Distant-talking speech recognition based on a 3-D Viterbi search using a microphone array. - Yamada, T. (IEEE Transactions on speech and audio processing)
This paper focuses on microphone arrays to realize distant-talking speech recognition in real environments. In distant-talking situations, users can speak at arbitrary positions while moving. Therefore, it,is very important for high quality speech acquisition using microphone arrays to localize a talker accurately. However, it is very difficult to localize a moving talker in noisy and reverberant environments. The talker localization errors result in performance degradation of speech recognition. One way to solve this problem is to integrate the speech recognition process and the talker localization into a unified framework. This paper proposes a new speech recognition algorithm based on a three-dimensional (3-D) Viterbi search. The 3-D Viterbi method extracts a direction-time sequence of parameter vectors by steering a beam to every direction in every frame, then finds the most likely path in a 3-D trellis space composed of talker directions, input frames and HMM states. This means that speech recognition and talker localization are performed simultaneously within a statistical framework. To evaluate the performance of the 3-D Viterbi method, recognition experiments for real environment data were carried out. The results confirmed that the 3-D Viterbi method drastically improves the recognition performance for the moving talker case as well as for the fixed-position talker case